2018
DOI: 10.1186/s12902-018-0295-6
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese patient with 11β-hydroxylase deficiency due to novel compound heterozygous mutation in CYP11B1 gene: a case report

Abstract: BackgroundCongenital adrenal hyperplasia (CAH) resulting from steroid 11β-hydroxylase deficiency (11β-OHD) is caused by mutations in the CYP11B1 gene. It is the second major form of CAH associated with hypertension and hypopotassemia. The aim of this study was to provide a genetic analysis of 11β-OHD in a Chinese family.Case presentationA 19-year-old Chinese man was clinically diagnosed with 11β-OHD. His initial clinical manifestations included precocious puberty, hyperpigmentation, hypertension, and hypopotas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…The 11β-hydroxylase ( CYP11B1 ) gene is located on chromosome 8q24.3, contains 9 exons and 8 introns, and consists of 503 amino acids [ 10 ]. It is a key enzyme responsible for the final step in cortisol biosynthesis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 11β-hydroxylase ( CYP11B1 ) gene is located on chromosome 8q24.3, contains 9 exons and 8 introns, and consists of 503 amino acids [ 10 ]. It is a key enzyme responsible for the final step in cortisol biosynthesis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genotypes of the CYP11B1 / CYP11B2 loci are in strong linkage disequilibrium [ 12 ]. The two synthesize 11β hydroxylase and aldosterone synthase, and then synthesize steroids, which play an important role in myocardial fibrosis, hypertension and arteriosclerosis [ 10 , 13 ]. Studies have shown that steroid metabolism induces the development of coronary artery disease [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Более чем в 95% случаев причиной ВДКН является недостаточность фермента 21-гидроксилазы. На втором месте находится гипертоническая форма ВДКН, которая проявляется при дефиците 11β-гидроксилазы и встреча-ется, по данным литературы, примерно у 1 из 100 000 новорожденных [2].…”
unclassified